Etude de l'entomofaune associée à la cochenille du manioc Phenacoccus manihoti Matile-Ferrero, en Côte d'Ivoire - Obame Minko, D.; Békon, AK. (Tropicultura, 2005)
Study of Insectfauna Associated to the Cassava Mealybug Phenacoccus manihoti Matile-Ferrero in Ivory Coast. Within the biocoenosis of cassava mealybug, Phenacoccus manihoti, in Ivory Coast, the presence of many predator and parasite insects is reported. The main predators of the mealybugs are Coccinellidae and particularly Scymnus couturieri. Among parasites, the most numerous are Encyrtidae hymenoptera. Some, like Epidinocarsis lopezi, attack directly mealybugs and are thus useful assistants. Others live as parasite on predators or parasites of mealybugs and so reduce the efficiency of those assistants. In addition, some other insects are present, whose role is not known. The authors note the relative abundance of all the collected species.